Uterine artery flow velocity waveforms before and after delivery in hypertensive disorders of pregnancy near term - Jose Ramon Duncan; Ana Marie Tobiasz; Zoran Bursac; Eric Vincent Rios-Doria; Mauro Humberto Schenone; Giancarlo Mari (Taylor & Francis Group, 2018)
Objective: To compare the uterine artery pulsatility index (UtAPI-AP) before labor and immediate postpartum (UtAPI-PP) in hypertensive disorders of pregnancy (HTNP) and normotensives near term. Methods: Pregnancies ≥36 weeks admitted for labor induction in our institution from October 2015 to October 2017 were included. We excluded active labor, multiple gestations, fetal demise, and those with inadequate uterine artery sampling. Our primary outcome was to compare the UtAPI-AP and UtAPI-PP between subjects with HTNP (gestational hypertension, preeclampsia with and without severe features) and normotensive participants. Our secondary outcomes were to compare the UtAPI-AP and UtAPI-PP by subgroups (severe HNTP, non-severe HTNP, and controls) and the UtAPI-PP in participants while on MgSO4 and after its discontinuation. A linear regression model was applied to test the above associations. A P < .05 was considered significant. Results: We included 108 women (HTNP = 71; controls = 37). The UtAPI-AP was higher in the HTNP group (.85 ± .3 vs. .71 ± .2; P < .001); however, the UtAPI-PP was not different between groups (1.11 ± .3 vs. 1.16 ± .4; P = .46). The UtAPI-AP was higher in the severe HTNP group than controls (P = .004), but there was no significant difference in the UtAPI-PP between subgroups. Our results remained unchanged after adjusting for confounders. The UtAPI while on MgSO4 and after its discontinuation was similar (P =  >.99). Conclusion: The increased UtAPI in patients with HTNP resolves soon after delivery. MgSO4 does not seem to have an effect on the UtAPI postpartum.